Pengembangan Inovasi Kurikulum di tingkat MTsN - Neka Zulwiddi; Iswantir M (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Nowadays, with this very advanced development of the age, the curriculum of education plays an important role in the overall structure of the national education system. Several state regulations have been implemented to enforce public policy. It is necessary for educational innovation, especially curricula, to align with current demands. If an educational institution does not develop or innovate a curriculum specifically for the educational institutions of the madrasah, then the institution will be lagging behind with the other education institutions. It has been determined that the curriculum of Islamic education has been formulated and regulated as an integral part of the educational policy framework, as established by many state or government regulations. This policy is formulated, and implemented by educational institutions specifically madrasah to deal with the public interest. It serves as a curriculum that consistently adapts to the changing needs of society. The experts define innovation as a fundamental aspect of education science, in the context of curriculum innovation in education. Innovators use different tactics while facing various challenges and problems during the implementation of the curriculum innovation process.